2014
DOI: 10.1556/jba.3.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of Internet-based problem shopping behaviour: The concept of online shopping addiction and its proposed predictors

Abstract: Background: Compulsive and addictive forms of consumption and buying behaviour have been researched in both business and medical literature. Shopping enabled via the Internet now introduces new features to the shopping experience that translate to positive benefits for the shopper. Evidence now suggests that this new shopping experience may lead to problematic online shopping behaviour. This paper provides a theoretical review of the literature relevant to online shopping addiction (OSA). Based on this selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 39 publications
4
113
0
14
Order By: Relevance
“…The scarce research conducted demonstrated specific psychological factors of motivation (e.g., exhaustive offers, immediate feelings) and a loss of control (e.g., low self-regulation), as well as addiction predictors differing only slightly from those of other specific cyberaddictions (i.e., female gender, negative emotional state, social anonymity, and cognitive overload) [48,49].…”
Section: Preliminary Results From Research Areas Of Internet Addictiomentioning
confidence: 99%
“…The scarce research conducted demonstrated specific psychological factors of motivation (e.g., exhaustive offers, immediate feelings) and a loss of control (e.g., low self-regulation), as well as addiction predictors differing only slightly from those of other specific cyberaddictions (i.e., female gender, negative emotional state, social anonymity, and cognitive overload) [48,49].…”
Section: Preliminary Results From Research Areas Of Internet Addictiomentioning
confidence: 99%
“…CBD is listed as "shopping addiction" in the appendix of the most recent version of The Diagnostic and Statistical manual of Mental Disorders (DSM-5, APA), but it is not a recognised as a distinct mental disorder due to insufficient evidence to establish the diagnostic criteria (American Psychiatric Association, 2013). Nonetheless, CBD is considered by many to constitute a behavioural addiction (Demetrovics and Griffiths, 2012;Lo and Harvey, 2012;Rose and Dhandayudham, 2014;Starcke et al, 2013). Like most addictive disorders, compulsive buying is characterised by both impulsive and compulsive aspects (Christenson et al, 1994;McElroy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although compulsive buying is not a distinct category in the DSM-5 (American Psychiatric Association, 2013), it is considered by many to be a behavioural addiction (Davenport, Houston and Griffiths, 2012;Demetrovics and Griffiths, 2012;Lo and Harvey, 2012;Rose and Dhandayudham, 2014;Starcke et al, 2013). Like most addiction disorders, compulsive buying is characterised by both impulsive and compulsive properties (Hollander and Allen, 2006;McElroy et al, 1994;Ridgway et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%